Methodology for teaching the folk dance of the Pasacalle rhythm/Metodología para la enseñanza de la danza folclórica del ritmo Pasacalle - Willian Andrés Cárdenas Toledo; July Elizabeth Fabre Cavanna (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The national rhythms are formed by urbanized versions of each nation, which create a set of musical genres that serve as the basis for the practice of specialized physical activity, while enriching the cultural heritage. The rescue of cultural traditions goes through specific actions that include Physical Education teachers. Therefore, the purpose of the research is to theoretically validate, through consultation with specialists, a methodological proposal for teaching folk dance with the Pasacalle rhythm. The research is of a descriptive-explanatory type with a prospective orientation. A methodological proposal was designed and validated through a survey by 15 national specialists. The proposal of a methodology for the teaching of the folkloric dance of the Pasacalle rhythm is acceptable according to the specialists consulted (w=0.513), presenting an average score in the indicators "relevance" (4.20: very adequate), "originality" (3 : adequate), "affordable" (4.27: very adequate) and "objective" (3.93: between adequate and very adequate). The proposal includes characteristics of a methodological strategy that contains a theoretical and methodological foundation, with a diagnostic phase and a planning phase, plus three stages that include the determination of the methodological steps, the design of an optional subject and the evaluation. methodology, as well as a group of contents and objectives to be implemented in the physical education class, plus teaching resources and skills with performance criteria.